2013
DOI: 10.1002/jgrb.50219
|View full text |Cite
|
Sign up to set email alerts
|

Radially anisotropic structure beneath the Shikoku Basin from broadband surface wave analysis of ocean bottom seismometer records

Abstract: We have analyzed broadband surface wave data from ocean bottom seismometers deployed in the Shikoku Basin in the northeastern Philippine Sea to determine the radially anisotropic uppermost mantle structure beneath this oceanic basin. We first applied noise correlation method to continuous microseismic records to obtain phase velocities for fundamental‐mode and first higher‐mode Rayleigh waves and fundamental‐mode Love waves at periods of 7–29 s. At longer periods, we applied an array analysis method to telesei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 96 publications
(189 reference statements)
4
82
0
Order By: Relevance
“…First, faster SH velocity anomalies at 150 km depth beneath the Pacific have been reported in several studies since the late 1980s [e.g., Cara and Lévêque, 1988;Nishimura and Forsyth, 1989;Montagner and Tanimoto, 1991;Ekström and Dziewoński, 1998;Gung et al, 2003;Nettles and Dziewoński, 2008], which are observed in all the models shown in Figure 8. The same kind of feature is also observed in the asthenosphere beneath the Philippine Sea Plate by a recent study using broadband ocean bottom seismometers [Takeo et al, 2013], which is also shown in all the models. Second, Gu et al [2005] reported that beneath the East Pacific Rise the faster axis of radial anisotropy changes from a vertical direction at~200-300 km depth to a horizontal direction at~100 km depth.…”
Section: 1002/2014jb011824supporting
confidence: 54%
“…First, faster SH velocity anomalies at 150 km depth beneath the Pacific have been reported in several studies since the late 1980s [e.g., Cara and Lévêque, 1988;Nishimura and Forsyth, 1989;Montagner and Tanimoto, 1991;Ekström and Dziewoński, 1998;Gung et al, 2003;Nettles and Dziewoński, 2008], which are observed in all the models shown in Figure 8. The same kind of feature is also observed in the asthenosphere beneath the Philippine Sea Plate by a recent study using broadband ocean bottom seismometers [Takeo et al, 2013], which is also shown in all the models. Second, Gu et al [2005] reported that beneath the East Pacific Rise the faster axis of radial anisotropy changes from a vertical direction at~200-300 km depth to a horizontal direction at~100 km depth.…”
Section: 1002/2014jb011824supporting
confidence: 54%
“…For example, higher-mode Rayleigh waves are observable and important in oceanic regions at periods shorter than ∼10-20 s, where the fundamental-mode Rayleigh wave is mainly sensitive to P-wave velocity in the ocean and higher-mode Rayleigh waves are sensitive to S-wave velocity in the crust and uppermost mantle (Ewing et al 1957). Previous studies analysed each mode of Rayleigh wave separately by applying group velocity filters (Harmon et al 2007;Yao et al 2011;Takeo et al 2013). The separation, however, becomes difficult for shorter interstation distances due to overlap between different modes.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of Rayleigh and Love waves in horizontal components is also difficult for short interstation distances or at long periods, where the Rayleigh and Love waves appear in the both radial and transverse components (Aki 1957). Although both Rayleigh and Love waves have been analysed in land (Bensen et al 2008;Nishida et al 2008) and oceanic regions (Mordret et al 2013a;Takeo et al 2013), this effect has not been accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Further north at the CLSC, both the crustal thickness (6-7 km) and lava composition are similar to that of fast-spreading midocean ridges (Jacobs et al, 2007;Pearce, 1995;Taylor and Martinez, 2003). The axial melt lens is present and sits at a depth of 1-2 km, similar to the fast-spreading East Pacific Rise (EPR).…”
Section: Geological Settingsmentioning
confidence: 84%
“…With increasing distance to the volcanic arc northward, the ELSC/VFR system shows decreasing subduction influence. Along the VFR and c-ELSC, the sampled lavas are highly vesicular and have an arc-like composition, characterized by low Mg number and a higher degree of depletion Pearce et al, 1994;Taylor and Martinez, 2003;Vallier et al, 1991). The crust along the VFR and c-ELSC is 8-9 km thick (Turner et al, 1999), and there exists a thick upper crustal region of low velocities (Jacobs et al, 2007).…”
Section: Geological Settingsmentioning
confidence: 98%